2021
DOI: 10.1038/s43856-021-00052-w
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a fully remote randomized clinical trial with cardiac monitoring

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has challenged researchers performing clinical trials to develop innovative approaches to mitigate infectious risk while maintaining rigorous safety monitoring. Methods In this report we describe the implementation of a novel exclusively remote randomized clinical trial (ClinicalTrials.gov NCT04354428) of hydroxychloroquine and azithromycin for the treatment of the SARS-CoV-2–mediated COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The adoption of digital health tools to develop and deploy digitally augmented trials has been rising steadily since the first fully remote decentralized trial in 2011 [ 6 - 8 ]. Recent studies have shown the benefits of remote monitoring using smartphones for assessing real-world behavior [ 9 , 10 ], for managing chronic pain [ 11 ], cancer care [ 12 ], diabetes [ 13 ], Parkinson symptom severity [ 14 ], and cardiovascular health [ 15 ] and for the delivery of remote interventions [ 16 ]. The COVID-19 pandemic has further accelerated this growth, enabling over 220 digitally augmented trials in 2021 alone [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of digital health tools to develop and deploy digitally augmented trials has been rising steadily since the first fully remote decentralized trial in 2011 [ 6 - 8 ]. Recent studies have shown the benefits of remote monitoring using smartphones for assessing real-world behavior [ 9 , 10 ], for managing chronic pain [ 11 ], cancer care [ 12 ], diabetes [ 13 ], Parkinson symptom severity [ 14 ], and cardiovascular health [ 15 ] and for the delivery of remote interventions [ 16 ]. The COVID-19 pandemic has further accelerated this growth, enabling over 220 digitally augmented trials in 2021 alone [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A strong agreement appeared between manually evaluated and AI-predicted QTc values (−1.76 ± 23.14 ms). Mayfield et al ( 34 ) described implementing a fully randomized clinical trial with cardiac monitoring. ECG collection was performed with the KardiaMobile 6L device.…”
Section: Resultsmentioning
confidence: 99%